PERAN KEJAKSAAN DALAM PENERAPAN RESTORATIVE JUSTICE TERHADAP PENYALAHGUNA NARKOTIKA (Studi Kasus di Kejaksaan Negeri Karawang) - Khoirunnissa, Zahra; Gagarin, M Gary; Abas, Muhammad (Legacy: Jurnal Hukum dan Perundang-Undangan, 2025)
Drug abuse constitutes a critical issue that impacts not only individuals but also society at large. As a criminal offense categorized as an extraordinary crime, its resolution requires a legal approach that goes beyond merely punitive measures. This study examines the role of the Karawang District Prosecutor's Office in implementing a restorative justice approach toward drug offenders, based on the Regulation of the Attorney General Number 15 of 2020 and the Guidelines of the Attorney General Number 18 of 2021. A juridical-empirical approachwas employedto analyze theactual legal practices inthe field, with datacollectedthrough interviews andlegal documents. The findings indicate that although restorative justice has begun to be implemented, its application in drug abuse cases remains very limited and faces several challenges, including lengthy procedures, inter-agency coordination issues, time constraints, and a lack of public understanding. This study highlights the crucial role of prosecutors as dominus litis in directing cases towardrehabilitation, as well as the need to strengthen institutional synergy and public education to achieve a more humane and solution- oriented form of justice. The case study of the Karawang District Prosecutor’s Office demonstrates that restorative justice holds significant potential as an alternative mechanism for resolving cases in a more equitable and recovery-focused manner.